2023
DOI: 10.1111/joor.13612
|View full text |Cite
|
Sign up to set email alerts
|

Use of suction electrodes for measurement of intrinsic tongue muscular endurance during lingual pressure generation

Reiko Ita,
Jin Magara,
Yuto Ochiai
et al.

Abstract: BackgroundLingual pressure (LP) generation is cooperatively controlled not only by the intrinsic tongue (I‐ton) muscles but also by hyoid muscle activation. However, the measurement of endurance and fatigue properties of I‐ton muscles is difficult due to the instability of electrodes.ObjectiveThe purpose of this study was to apply suction electrodes to measure electromyograms (EMGs) of I‐ton muscle and to evaluate integrated EMG amplitude (iEMG) and mean power frequency (MPF) of EMG in the I‐ton and hyoid musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In particular, TPG that maintains 60% of maximal tongue pressure for 30 s is a significant load for the tongue muscles, and the possibility that the submental sEMG signals contain a tongue muscle activity component cannot be ruled out [30]. Furthermore, report has shown that the intrinsic tongue muscles may easily fatigue during TPG, but tongue pressure may be maintained by increasing hyoid muscle activity [31]. Thus, it may be difficult to estimate the timing and degree of fatigue of the hyoid muscles in TPG from the sEMG signals in the anterior neck alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, TPG that maintains 60% of maximal tongue pressure for 30 s is a significant load for the tongue muscles, and the possibility that the submental sEMG signals contain a tongue muscle activity component cannot be ruled out [30]. Furthermore, report has shown that the intrinsic tongue muscles may easily fatigue during TPG, but tongue pressure may be maintained by increasing hyoid muscle activity [31]. Thus, it may be difficult to estimate the timing and degree of fatigue of the hyoid muscles in TPG from the sEMG signals in the anterior neck alone.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may be difficult to estimate the timing and degree of fatigue of the hyoid muscles in TPG from the sEMG signals in the anterior neck alone. To clarify the relationship between changes in muscle activity patterns detected by NED and FT, it will be necessary to consider simultaneous measurement of tongue muscle activities in TPG by suction electrodes [31] or other means, or to employ the shaker exercise [8] as FT in the future.…”
Section: Discussionmentioning
confidence: 99%